VD_FINDINFO HC / 2023 / 592 vom 11. September 2023 - VD Tribunal cantonal (2023)
PRIX, VENTE, COMPENSATION DE CRÉANCES, LIVRAISON, DOMMAGES-INTÉRÊTS, PAIEMENT | 1 al. 1 CO, 120 CO, 191 CO, 42 al. 2 CO, 29 al. 2 Cst.